Antituberculosis Activity Test of N-p-Methylbenzyl-p-coumaramide (MBC) Against M. tuberculosis H37Rv - Wela, Nasriadi Dali; Wela, Arniah Dali; Dali, Seniwati; Amalia, Hilda Ayu Melvi (Al-Kimia, 2020)
An antituberculosis activity test of N-p-Methylbenzyl-p-coumaramide (MBC) against M. tuberculosis H37Rv has been carried out. The purpose of this study was to determine the antituberculosis activity of MBC against M. tuberculosis H37Rv. The study was conducted using agar diffusion method. The test solution was prepared by dissolving MBC in 20 mL Ogawa medium to a final concentration of 0.25; 0.50; 1; and 2 mg/L. PDA media that had been inoculated with M. tuberculosis H37Rv (seeded agar) were poured over the base layer on the petridish surface. Paper disks that have been immersed in the test solution were put symmetrically on the seeded agar. Furthermore, the seeds were incubated at 37 oC for 48 hours. Then the diameter of the inhibition zone was measured to the accuracy of 0.5 mm with a ruler. The results showed that MBC has biological activity as an antituberculosis. MBC can inhibit the growth of M. tuberculosis H37Rv at a concentration of 0.25; 0.50; 1; and 2 mg/L with a diameter of inhibitory zones respectively 8.9; 13.7; 18.5; and 21.3 mm. This showed that the inhibition of MBC on the growth of M. tuberculosis H37Rv increased with increasing concentration of MBC used.